Early and accurate detection of bacterial isolates from dental plaque in subjects with primary, mixed, and permanent dentition by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry technique - Srivastava, Amitabh; Saha, Sonali; Sahu, Chinmoy (Journal of Indian Society of Periodontology, 2020)
Background: Bacterial colonization of dentition in different age groups can impact prognosis in different dental diseases. Latest diagnostic technique such as matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF) is increasingly being used for accurate identification of bacteria. This study was undertaken to evaluate the MALDI-TOF MS technique to identify bacterial pathogens from dental plaques in subjects with primary, mixed, and permanent dentition. Materials and Methods: The study included 150 subjects of different age groups and were divided into three groups - Group A: Subjects with primary dentition (n = 50), Group B: Subjects with mixed dentition (n = 50), and Group C: Subjects with permanent dentition (n = 50). Subgingival dental plaque samples were collected from buccal and lingual surfaces of premolar and molar teeth. Clinical parameters such as gingival index were recorded. Samples were cultured in routine aerobic and anaerobic medium. Bacterial growths were assessed by semiquantitative methods. Bacterial isolates were confirmed by MALDI-TOF MS technique. Results: MALDI-TOF MS detected all the culture-grown bacteria. In primary dentition group, purple and yellow complex bacteria predominated. Streptococcus spp. was the predominant bacteria (51%) followed by Escherichia coli (19%) and Veillonella spp. (19%). In mixed dentition and permanent group also, Streptococcus spp. was predominant (46%) followed by Veillonella spp. (24%) and E. coli(19%). However, in both groups, orange complex bacteria (bridge complex) such as Prevotella nigrescens and red complex bacteria (Porphyromonas gingivalis, 3%) were seen. For majority of bacteria, the load increased with age. Conclusions: The bacterial isolates showed a distinct age-specific colonization. The use of advanced technique such as MALDI-TOF MS is helpful in the detection of periodontal pathogens, and the effective oral health programs can be implemented to minimize the risk of periodontal diseases.